The Norton anthology of literature by women The tradition in English - 20160731 frey50; Gilbert, Sandra M.; Gubar, Susan (W. W. Norton & Company, Inc. New York, 1985)
Contains selections written by over 150 women authors from English-speaking countries. Ranges from the fourteenth century to the present.
Julian Of Nortwich - Margery Kempe - Queen Elizabeth I - Mary Sidney Herbert - Amelia Lanier - Anne Bradstreet - Margaret Cavendish - Jane Lead - Katherine Philips - Mary Rolandson - Aphra Behn - Landy Mary Chudleigh - Anne Killigrew - Anne Finch - Mary Astell - Lady Mary Wortley Montagu - Charlotte Smith - Fanny Burney -Phillis Wheatley - Marry Wollstonecraft - Maria Edgeworth - Dorothy Wordsworth - Jane Austen - Rebecca Cox Jackson - Mary Shelley - Sojourner Truth - Elizabeth Barrett Browning - Margaret Fuller - Elizabeth Cleghorn Gaskell - Harriet Beecher Stowe - Elizabeth Candy Station - Charlotte Bronte - Emily Bronte - Linda Brent - George Eliot - Florence Nightingale - Elizabeth Drew Stoddard - Frances E. W. Harper - Harriet E. Adams Wilson - Emily Dickinson - Christina Rossetti - Rebecca Harding Davis - Louisa May Alcott - Alice Meynell - Alice James - Sarah Orne Jewett - Kate Chopin - Mary E. Wilkins Freeman - Lady Augusta Gregory - Olive Schreiner - Carlotte Perkins Gilman - Mary Elizabeth Coleridge - Edith Wharton - May Sinclair - Charlotte Mew - Henry Handel Richardson - Ellen Glasgow - Willa Cather - Dorothy Richardson - Amy Lowell - Gertrude Stein - Alice Dunbar-Nelson - Anna Hempstead Branch - Virginia Woolf - Susan Glaspell - Katharine Susannah Prichard - Anna Wickham - Elinor Wylie - Isak Dinesen - Anzia Yezierska - "Radclyffe Hall - H. D. (Hilda Doolittle) - Edith Sitwell - Marianne Moore - Katherine Mansfield - Mourning Dove - Katherine Anne Porter - Edna St. Vincent Millay - Djuna Barnes - Rebecca West - Dorothy Parker - Jean Rhys - Louise Bogan - Ruth Pitter - Elizabeth Bowen - Meridel Le Sueur - Zora Neale Hurston - Stevie Smith - Anais Nin - Kay Boyle - Lillian Hellman - Kathleen Raine - Dorothy Livesay - Eudora Welty - Elizabeth Bishop -Josephine Miles - Mary McCarthy - May Sarton - Muriel Rukeser - Tillie Olsen - Ruth Stone - Margaret Walker - Judith Wright - P. K. Page - Carson McCullers - Gwendolyn Brooks - Muriel Spark - Shirley Jackson - Doris Lessing - May Swenson - Eleanor Ross Taylor - Grace Paley - Nadine Gordimer - Denise Levertov - Flannery O'Connor - Carolyn Kizer - Maxine W. Kumin - Margaret Laurence - Anne Sexton - Maya Angelou - Ursula K. Le Guin - Adrienne Rich - Lorraine Hansberry - Toni Morrison - Alice Munro - Sylvia Plath - Edna O'Brien - Anne Stevenson - Fleur Adcock - Kamala Das - Audre Lorde - Lucille Clifton - Marge Piercy - Joanna Russ - Diane Wakoski - Joyce Carol Oates - Margaret Atwood - Toni Cade Bambara - Margaret Drabble - Angela Carter - Judy Grahn - Maxine Hong Kingston - Ama Ata Aidoo - Erica Jong - Louise Gluck - Susan Griffin - Alice Walker - Leslie Marmon Silko
Includes bibliographical references and index
Keywords: American literature -- Women authors; English Literture -- Women authors